Clinical Profile of Patients with Carcinoma Cervix in a Tertiary Level Hospital - Zebunnesa, Moshammat; Karim, Mohammad Masud; Dhar, Satyajit; Nessa, Kamrun; Begum, Kohinoor (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Cervical carcinoma is a preventable condition and over 95% of patients with early carcinoma cervix can be cured. But still women dying from malignant disease of all kinds the cervix is the common organ primarily involved. The study was conducted to find out the predisposing factors of carcinoma cervix in our population and to scrutinize the patients in early stages, so that measures can be taken to prevent it. After approval of ethical committee and informed written consent fifty patients from Dhaka Medical College hospital were included in this study from January 2003 to December 2003. Among the 50 patients 36 were between 31to 50 years, 42 patients present with blood stained per vaginal discharge and 40 present with post-coital bleeding. Regarding identifiable risk factors early age of 1st intercourse was most common followed by multiparity. Ninety four percent of patients had squamous cell carcinoma and reminder were adenocarcinoma. Incidence of carcinoma cervix can be decreased by health education with special attention to risk factors and morbidity and mortality can be reduced by detection of cases in early stage when it is still curable. J Bangladesh Coll Phys Surg 2017; 35(3): 110-114